Zirconium carbide nanofiber aerogel as well as preparation method and application thereof
By simplifying the preparation process of zirconium carbide nanofiber aerogels and using electrospinning technology of zirconium carbide ceramic organic precursors and binders, the problems of insufficient high-temperature thermal insulation performance and difficult to control fiber diameter in the prior art are solved, and the problem of insufficient high-temperature thermal insulation performance and difficult to control fiber diameter in the prior art is realized. The performance of efficient zirconium carbide nanofiber aerogel materials has been improved.
Patent Information
- Application Number
- CN202411330215.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
The existing zirconium carbide nanofiber aerogel materials have insufficient thermal insulation performance at high temperatures, complex processes and difficult to control fiber diameters, resulting in unstable performance.
The zirconium carbide ceramic organic precursor is mixed with a binder, and the spinning liquid is prepared by electrospinning process, dried and heat-treated to obtain zirconium carbide nanofiber aerogel, simplifying the process and controlling the fiber diameter.
It has achieved the high-temperature thermal insulation performance of zirconium carbide nanofiber aerogel, with temperature resistance up to above 2000℃, thermal conductivity coefficient ≤0.04W/(m·K), fiber diameter can be controlled below 100nm, density ≤0.02g/cm3, suitable for in the field of aerospace and thermal insulation materials.
Smart Images

Figure CN119263842A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel materials, and in particular to a zirconium carbide nanofiber aerogel and a preparation method and application thereof. Background Art
[0002] Aerogel pores have a diameter of several hundred nanometers, a porosity of over 95%, and the dispersed phase is air. These characteristics make aerogel materials have broad application potential in thermal, acoustic, optics, microelectronics, and particle detection. At present, the most widely used field of aerogel is still the field of thermal insulation, because the unique nanostructure of aerogel can effectively reduce convection conduction, solid phase conduction, and thermal radiation. Existing studies have proven that aerogel is an effective thermal insulation material, but the maximum temperature resistance limit of the high-temperature resistant aerogel materials reported so far does not exceed 1100°C under long-term actual use. ZrC has a melting point of more than 3000°C and a low vapor pressure, and previous studies have shown that ZrC has excellent ablation resistance and can be used in working environments of 2000°C or even higher.
[0003] The prior art has a literature report that: after dissolving zirconium n-propoxide in ethanol, acetylacetone is added thereto to obtain a zirconium source solution; sucrose is dissolved in N,N-dimethylformamide, and 4-8wt% polyvinyl pyrrolidone is added at room temperature to obtain a sucrose solution; the zirconium source solution is added to the sucrose solution to obtain a spinning solution, and electrospinning is performed to obtain fibers; the fibers are heat-treated to obtain ZrO 2 / C nanofibers; then ZrO 2 / C fiber made of ZrO 2 / C fiber solution, and then add dispersant and binder to the solution, mix, freeze-dry, and obtain ZrO 2 / C fiber aerogel; then ZrO 2 / C fiber aerogel is heat treated to obtain ZrC fiber aerogel material. However, the above method has many steps and complicated process, and it is difficult to obtain a spinning solution with stable performance by using the traditional process of preparing spinning solution. Sucrose as a carbon source will cause the fibers to adhere to each other and produce bubbles during the sintering process, which has a great impact on the sintering and forming of zirconium carbide nanofibers; and the diameter of zirconium carbide fibers is also difficult to be effectively controlled. Summary of the invention
[0004] The main purpose of the present invention is to provide a zirconium carbide nanofiber aerogel and its preparation method and application. The technical problem to be solved is how to provide a zirconium carbide nanofiber aerogel so that the product performance has excellent high temperature resistance and heat insulation performance, and its temperature resistance can reach above 2000°C, and the thermal conductivity coefficient is ≤0.04W / (m·K); at the same time, the obtained product is lightweight, and the density is ≤0.02g / cm 3; Furthermore, under the condition of better process control, the diameter of the fiber can be effectively controlled; in some embodiments, the fiber diameter can be controlled below 100nm, or even up to 70nm.
[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a method for preparing zirconium carbide nanofiber aerogel proposed in the present invention, the method comprises the following steps:
[0006] S11 adding zirconium carbide ceramic organic precursor into a binder and stirring evenly to obtain a spinning solution;
[0007] S12 electrospinning the spinning solution, drying, and pressing to obtain a zirconium carbide nanofiber aerogel blank;
[0008] S13 heat treatment to obtain zirconium carbide nanofiber aerogel.
[0009] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0010] Preferably, in the aforementioned preparation method, the steps for preparing the zirconium carbide ceramic organic precursor are as follows:
[0011] S21: adding zirconium oxychloride into a mixed solvent of water and ethanol to cause a hydrolysis reaction;
[0012] S22 adds acetylacetone to the hydrolysis reaction solution to react and obtain enol acetylacetone;
[0013] S23 adding butanediol to the reaction solution containing the enol acetylacetone to perform alcohol exchange;
[0014] S24 is evaporated to obtain an organic precursor of zirconium carbide ceramic.
[0015] Preferably, in the aforementioned preparation method, the molar ratio of the zirconium oxychloride, the mixed solvent, acetylacetone and butanediol is 1:2-4:3-5:1-3.
[0016] Preferably, in the aforementioned preparation method, the binder comprises anhydrous ethanol and polyvinyl pyrrolidone; based on the mass of the anhydrous ethanol being 100%, the mass percentage of the polyvinyl pyrrolidone is 5-20%.
[0017] Preferably, in the aforementioned preparation method, in the spinning solution, the mass ratio of the zirconium carbide ceramic organic precursor to the anhydrous ethanol is 1:0.4-0.6.
[0018] Preferably, in the aforementioned preparation method, the process parameters of the electrospinning are as follows: voltage is 25-30 Kv, injection speed is 0.10-0.15 ml / h, and distance is 6-8 cm.
[0019] Preferably, in the aforementioned preparation method, the heat treatment step is as follows:
[0020] S71 is kept at 500-700℃ under vacuum for 1-2h;
[0021] S72, under vacuum conditions, heat to 1000-1500°C at a rate of ≥1°C / min and keep warm for 1-2h;
[0022] S73 Cool down to room temperature.
[0023] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the present invention, a zirconium carbide nanofiber aerogel is proposed, the diameter of which is ≤100nm and the density is
[0024] ≤0.02g / cm 3 , thermal conductivity ≤0.04W / (m·K).
[0025] Preferably, the aforementioned zirconium carbide nanofiber aerogel is prepared by the aforementioned method for preparing zirconium carbide nanofiber aerogel.
[0026] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: According to the present invention, an application of the aforementioned zirconium carbide nanofiber aerogel in the field of aerospace, high temperature resistant materials or thermal insulation materials is proposed.
[0027] By means of the above technical solution, the zirconium carbide nanofiber aerogel and its preparation method and application provided by the present invention have at least the following advantages:
[0028] The zirconium carbide nanofiber aerogel provided by the present invention is prepared by preparing a zirconium carbide ceramic organic precursor, mixing it with a binder to obtain a spinning solution; then spinning is performed by an electrostatic spinning process, and after drying and pressing, a zirconium carbide nanofiber aerogel blank is obtained; finally, the zirconium carbide nanofiber aerogel is obtained by heat treatment. The present invention breaks through the constraints of traditional technology and introduces organic polymer technology into the preparation of zirconium carbide nanofibers, so that the zirconium element exists in the form of zirconium carbide in the precursor stage, avoiding the step of zirconium carbide being transferred from zirconium oxide, greatly simplifying the aerogel process, and also expanding the application scenarios of zirconium carbide organic precursors; moreover, through the technical solution of the present invention, the spinning solution is electrostatically spun to obtain a zirconium carbide nanofiber aerogel with excellent comprehensive performance, and the obtained product performance has excellent high temperature resistance and heat insulation performance, and its temperature resistance can reach more than 2000°C, and the thermal conductivity coefficient is ≤0.04W / (m·K); at the same time, the obtained product is lightweight, and the density is ≤0.02g / cm 3 ; The zirconium carbide nanofiber aerogel prepared by the present invention also has excellent flexibility.
[0029] Furthermore, the present invention precisely controls the process parameters of electrospinning so that when the voltage, injection speed and distance are in an optimal state at the same time, the obtained fiber diameter can be refined to less than 100nm, or even reach 70nm, so that it has more excellent performance; it can be widely used in the aerospace field, high temperature resistant material field or thermal insulation material field, and used as a high temperature resistant thermal insulation material with excellent performance.
[0030] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a process flow chart of the zirconium carbide nanofiber aerogel of the present invention;
[0032] Figure 2 This is a SEM photograph of the zirconium carbide nanofiber aerogel in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a zirconium carbide nanofiber aerogel and its preparation method and application, its specific implementation method, structure, characteristics and effects proposed by the present invention in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0034] The present invention provides a method for preparing zirconium carbide nanofiber aerogel. The process flow is as shown in the attached figure. Figure 1 As shown, it uses zirconium oxychloride, acetylacetone and butanediol as raw materials, and uses rotary evaporation method to synthesize linear high molecular polymer ZrC ceramic organic precursor through alcoholization of zirconium oxychloride and synthesis of enol acetylacetone, and alcohol exchange reaction with butanediol; then, it is prepared into spinning solution for electrostatic spinning and heat treatment; that is, the present invention uses zirconium carbide organic precursor to prepare zirconium carbide nanofiber aerogel through electrostatic spinning process. Specifically, it includes the following steps:
[0035] The first step is to prepare a binder and an organic precursor of zirconium carbide ceramics.
[0036] In the preparation of the binder, the carbon source is preferably polyvinyl pyrrolidone (PVP), which is dissolved in anhydrous ethanol and stirred evenly. As a synthetic water-soluble polymer compound, polyvinyl pyrrolidone has the general properties of water-soluble polymer compounds, such as colloid protection, film-forming property, adhesion, hygroscopicity, solubilization or coagulation, etc.; it does not include carbon sources such as sucrose, which can avoid the effect of sucrose as a carbon source on the performance of the fiber. The preferred mass ratio of polyvinyl pyrrolidone (PVP) and anhydrous ethanol is as follows: the mass percentage of the polyvinyl pyrrolidone is 5-20% based on the mass of anhydrous ethanol as 100%. By controlling the type of carbon source material in the binder, it is avoided that the carbon source contains raw materials such as sucrose, thereby providing a guarantee for the performance of the final product; at the same time, by controlling the mass concentration of the binder, the prepared spinning solution has an appropriate concentration for easy spinning quality control.
[0037] The use of zirconium carbide ceramic organic precursor in the technical scheme is the key point of the present invention. The zirconium carbide ceramic organic precursor can be purchased on the market or prepared by conventional methods in the prior art. In order to better achieve the technical effect of the present invention and effectively control the diameter of the fiber to be ≤100nm, the molecular structure of the zirconium carbide ceramic organic precursor of the present invention is preferably a linear high molecular polymer structure ZrC ceramic organic precursor. In a specific embodiment of the present invention, the specific preparation steps are as follows: first, zirconium oxychloride is added to a mixed solvent of water and ethanol under normal temperature and pressure conditions to undergo a hydrolysis reaction; wherein the molar ratio of water to ethanol in the mixed solvent is 1:1 to 3; further preferably 1 to 1.5 to 2.5; further preferably 1:2; in this step, the chlorine element in the zirconium oxychloride is partially or completely replaced by a hydroxyl group so that it contains a hydroxyl group to obtain hydroxyl zirconium oxide and / or hydroxyl zirconium oxychloride; then acetylacetone is added to the hydrolysis reaction solution to carry out a group replacement reaction to obtain Enol acetylacetone; in this step, hydroxy zirconium oxide and / or hydroxy zirconium oxychloride react with acetylacetone to replace the hydrogen atoms on the hydroxyl group; then butanediol is added to the reaction solution containing the enol acetylacetone to undergo an alcohol exchange reaction, that is, part of the hydrogen elements on the hydroxyl group are replaced with butanediol groups; finally, the ethanol in the reaction solution is evaporated by rotary evaporation, and at the same time, the butanediol groups replaced on the product undergo condensation reactions with each other to form a polymer structure, thereby obtaining a linear molecular structure of a high molecular weight polymer zirconium carbide ceramic organic precursor. The reactions in the above steps can all occur at room temperature and pressure, and the present invention does not specifically limit the reaction conditions.
[0038] In order to better balance the material relationship, promote the occurrence of the above reaction, and enable it to obtain the target product in a higher yield, the molar ratio of the zirconium oxychloride, the mixed solvent, acetylacetone, and butanediol is preferably 1:2-4:3-5:1-3; the further preferred molar ratio is 1:2.5-3.5:3.5-4.5:2-3; the further preferred molar ratio is 1:3:4:2.
[0039] After the binder and the zirconium carbide ceramic organic precursor are prepared, the zirconium carbide ceramic organic precursor is added to the binder and stirred evenly to obtain a spinning solution. The mixing and stirring in this step is performed according to conventional operations, as long as the binder and the zirconium carbide ceramic organic precursor can be evenly mixed, and the present invention does not make specific limitations on this.
[0040] When preparing the spinning solution, the ratio of the zirconium carbide ceramic organic precursor to the binder is controlled so that the spinning solution is in a better spinning operation state; the present invention preferably has a mass ratio of the zirconium carbide ceramic organic precursor to the anhydrous ethanol contained in the binder of 1:0.4-0.6; a further preferred mass ratio is 1:0.45-0.55; and a further preferred mass ratio is 1:0.5.
[0041] Then the above-prepared spinning solution is spun, and the fibers obtained by spinning are dried and pressed to obtain the zirconium carbide nanofiber aerogel blank. The present invention preferably spins the spinning solution by an electrostatic spinning process. Electrostatic spinning of the spinning solution is also a key step of the present invention, and its specific process parameters are set as follows: the voltage is 25-30Kv, the injection speed is 0.10-0.15ml / h, and the distance is 6-8cm. Among the above three process parameters, only when they are simultaneously within the above-mentioned preferred operating range can the zirconium carbide nanofiber aerogel prepared by the present invention have better performance and the fiber diameter can be better controlled; the fiber diameter obtained when the above process parameters are combined and controlled is uniformly distributed, and the fiber diameter is very fine. The spinning voltage should not be too low, otherwise the diameter of the fiber obtained by spinning is larger; the spinning voltage should not be too high. On the one hand, the spinning is discontinuous when the voltage is too high, and on the other hand, the equipment is limited by the high voltage. The spinning solution injection speed should not be too slow, otherwise the spinning will be discontinuous; the spinning solution injection speed should not be too fast, otherwise the spinning quality will be poor, balls will easily appear, and there will be more impurities. The spinning distance should not be too close, otherwise the spinning will be uneven; the spinning distance should not be too far, otherwise the diameter of the obtained fiber will become larger. The present invention further preferably has a voltage of 26 to 30Kv, an injection speed of 0.11 to 0.13ml / h, and a distance of 6.5 to 7.5cm; further preferably has a voltage of 26 to 30Kv, an injection speed of 0.12ml / h, and a distance of 7.0cm; further preferably has a voltage of 30Kv, an injection speed of 0.12ml / h, and a distance of 7.0cm. The drying and pressing described in the present invention can be carried out by conventional technical means in the art, and are not specifically limited in the present invention.
[0042] Finally, the zirconium carbide nanofiber aerogel blank obtained by spinning is heat treated to obtain the zirconium carbide nanofiber aerogel.
[0043] In order to ensure the final quality of the product, the preferred heat treatment of the present invention includes the following steps: first, pyrolysis and debinding, that is, keeping warm at 500-700°C for 1-2 hours under vacuum conditions to remove the binder, such as the colloidal components in polyvinyl pyrrolidone, so that it forms a pore structure of a three-dimensional porous network structure, which reduces its density on the one hand and reduces its thermal conductivity on the other hand, thereby improving its thermal insulation. It is further preferred that the pyrolysis and debinding process is to keep warm at 600-700°C for 1 hour under vacuum conditions. The vacuum condition here is a conventional vacuum, which is not specifically limited, and generally the absolute pressure is controlled to be 0.1-1 Pa.
[0044] After the binder is removed, the temperature is quickly raised to a preset temperature for insulation to control the crystallization process and ensure that the diameter of the fiber can be controlled at a relatively fine level. The present invention preferably controls the heating rate to be ≥1°C / min. When the heating rate is too slow, the crystallization time will be prolonged, making the fiber diameter thicker, while if the heating rate is too fast, it will be limited by the equipment. At the same time, the present invention preferably controls the insulation temperature to 1000-1500°C. The insulation temperature should not be too low, otherwise it will make the zirconium carbide particles difficult to crystallize; the insulation temperature should not be too high, otherwise it will cause the fiber to shrink more and the fiber diameter to become thicker.
[0045] The invention synthesizes a linear molecular structure high molecular polymer zirconium carbide ceramic organic precursor, then mixes and dissolves the zirconium carbide ceramic organic precursor with polyvinyl pyrrolidone (PVP) and anhydrous ethanol to prepare a ZrC nanofiber spinning solution; then spins the solution into ZrC nanofiber filaments through an electrostatic spinning process controlled by specific combination parameters; forms a zirconium carbide nanofiber aerogel blank after drying and pressing; and finally obtains a zirconium carbide nanofiber aerogel material through heat treatment.
[0046] The present invention also provides a zirconium carbide nanofiber aerogel, the diameter of which is ≤100nm and the density is
[0047] ≤0.02g / cm 3 , thermal conductivity ≤ 0.04W / (m·K), which can be prepared by the above-mentioned preparation method of zirconium carbide nanofiber aerogel. This material has low density and low thermal conductivity, and has good application prospects in the fields of aerospace, high temperature resistant materials or thermal insulation materials.
[0048] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0049] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0050] Example 1
[0051] This embodiment prepares a zirconium carbide nanofiber aerogel, and the specific steps are as follows:
[0052] 1) Preparation of organic zirconium carbide precursor: first, in terms of molar quantity, mix 1 part of water and 2 parts of ethanol to obtain a mixed solvent; then add 1 part of zirconium oxychloride to the mixed solvent for alcoholization reaction for about 1 hour; add 4 parts of acetylacetone to the reaction solution and react for about 1 hour to obtain enol acetylacetone; add 2 parts of butanediol to the reaction solution and react for 1 hour; remove the ethanol by rotary evaporation to obtain an organic zirconium carbide ceramic precursor.
[0053] 2) Preparation of binder: Weigh 50 g of anhydrous ethanol and then weigh 10 g of polyvinyl pyrrolidone (PVP), add them to the anhydrous ethanol, stir evenly, and obtain a binder.
[0054] 3) Preparation of spinning solution: Weigh 100 g of the ZrC ceramic organic precursor prepared in step 1), add it to all the binders prepared in step 2), stir evenly, and obtain a spinning solution.
[0055] 4) Electrospinning: The spinning solution obtained in step 3) is sucked into the syringe of the electrospinning device, and the electrospinning parameters are set for electrospinning; the electrospinning parameters are as follows: voltage 30 KV, injection speed 0.12 ml / h, distance 7 cm.
[0056] 5) Preparation of zirconium carbide nanofiber aerogel blank: The spinning in step 4) is dried in an oven at 50-150° C., and then pressed into a target shape at room temperature to obtain a zirconium carbide nanofiber aerogel blank.
[0057] 6) Heat treatment: Place the zirconium carbide nanofiber aerogel blank prepared in step 5) in a vacuum furnace with a pressure of 0.1 to 1 Pa, heat it to 600°C and keep it for 1 hour to remove the colloid in the PVP; then, quickly heat the vacuum furnace to 1500°C at a rate of 1°C / min and keep it for 1 hour; finally, naturally cool it to room temperature to obtain the zirconium carbide nanofiber aerogel material.
[0058] The SEM photo of the zirconium carbide nanofiber aerogel obtained in this example is shown in the attached figure. Figure 2 shown.
[0059] After testing, the zirconium carbide nanofiber aerogel obtained in the embodiment of the present invention has a diameter of 100nm and a density of 0.02g / cm 3 , the thermal conductivity is 0.04W / (m·K).
[0060] Example 2
[0061] The process steps are the same as those in Example 1, except that: in step 1), ethanol is 1 part; the test results are shown in Table 1.
[0062] Example 3
[0063] The process steps are the same as those in Example 1, except that: in step 1), the amount of ethanol is 3 parts; the test results are shown in Table 1.
[0064] Example 4
[0065] The process steps are the same as those in Example 1, except that: in step 1), the amount of acetylacetone is 3 parts; the test results are shown in Table 1.
[0066] Example 5
[0067] The process steps are the same as those in Example 1, except that: in step 1), the amount of acetylacetone is 5 parts; the test results are shown in Table 1.
[0068] Example 6
[0069] The process steps are the same as those in Example 1, except that: in step 1), the amount of butanediol is 1 part; the test results are shown in Table 1.
[0070] Example 7
[0071] The process steps are the same as those in Example 1, except that: in step 1), the amount of butanediol is 3 parts; the test results are shown in Table 1.
[0072] Example 8
[0073] The process steps are the same as those in Example 1, except that: in step 2), the amount of polyvinyl pyrrolidone (PVP) used is 7.5 g; the test results are shown in Table 1.
[0074] Example 9
[0075] The process steps are the same as those in Example 1, except that: in step 2), the amount of polyvinyl pyrrolidone (PVP) used is 2.5 g; the test results are shown in Table 1.
[0076] Example 10
[0077] The process steps are the same as those in Example 1, except that: in step 1), the amount of ethanol is 1.5 parts; in step 5), the debinding process temperature is 500° C. and the temperature is kept for 2 hours; the test results are shown in Table 1.
[0078] Embodiment 11
[0079] The process steps are the same as those in Example 1, except that: in step 1), the amount of ethanol is 2.5 parts; in step 5), the debinding process temperature is 700° C.; the insulation temperature after rapid heating is 1000° C. for 2 hours; and the test results are shown in Table 1.
[0080] Example 12
[0081] The process steps are the same as those in Example 1, except that: in step 1), the amount of acetylacetone is 3.5 parts; the test results are shown in Table 1.
[0082] Embodiment 13
[0083] The process steps are the same as those in Example 1, except that: in step 1), the amount of acetylacetone is 4.5 parts; the test results are shown in Table 1.
[0084] Embodiment 14
[0085] The process steps are the same as those in Example 1, except that: in step 1), the amount of butanediol is 1.5 parts; the test results are shown in Table 1.
[0086] Embodiment 15
[0087] The process steps are the same as those in Example 1, except that: in step 1), the amount of butanediol is 2.5 parts; the test results are shown in Table 1.
[0088] Example 16
[0089] The process steps are the same as those in Example 1, except that: in step 3), the amount of ZrC ceramic organic precursor used is 124 parts; the test results are shown in Table 1.
[0090] Embodiment 17
[0091] The process steps are the same as those in Example 1, except that: in step 3), the amount of ZrC ceramic organic precursor used is 110 parts; the test results are shown in Table 1.
[0092] Embodiment 18
[0093] The process steps are the same as those in Example 1, except that: in step 3), the amount of ZrC ceramic organic precursor used is 90 parts; the test results are shown in Table 1.
[0094] Embodiment 19
[0095] The process steps are the same as those in Example 1, except that: in step 3), the amount of ZrC ceramic organic precursor used is 84 parts; the test results are shown in Table 1.
[0096] Embodiment 20
[0097] The process steps are the same as those in Example 1, except that in step 4), the voltage is 28 KV, the injection speed is 0.11 ml / h, and the distance is 6.5 cm; the test results are shown in Table 1.
[0098] Embodiment 21
[0099] The process steps are the same as those in Example 1, except that in step 4), the injection speed is 0.13 ml / h and the distance is 7.5 cm. The test results are shown in Table 1.
[0100] Embodiment 22
[0101] The process steps are the same as those in Example 1, except that the zirconium carbide precursor is purchased from the market; the test results are shown in Table 1.
[0102] Embodiment 23
[0103] The process steps are the same as those in Example 1, except that: the zirconium carbide precursor is prepared according to the following method: 1 mole part of zirconium oxychloride and 4 moles of acetylacetone are weighed and mixed in an argon atmosphere; the mixed solution is heated at 100° C. for 2 to 5 hours in an argon atmosphere, deionized water is added thereto, and stirring is continued for 6 to 24 hours to obtain the zirconium carbide precursor; the test results are shown in Table 1.
[0104] Embodiment 24
[0105] The process steps are the same as those in Example 1, except that: Step 4) the electrospinning parameters are as follows: voltage 26 KV, injection speed 0.12 ml / h, distance 7 cm; the test results are shown in Table 1.
[0106] Embodiment 25
[0107] The process steps are the same as those in Example 1, except that: Step 4) the electrospinning parameters are as follows: voltage 30 KV, injection speed 0.10 ml / h, distance 7 cm; the test results are shown in Table 1.
[0108] Embodiment 26
[0109] The process steps are the same as those in Example 1, except that: Step 4) the electrospinning parameters are as follows: voltage 30 KV, injection speed 0.14 ml / h, distance 7 cm; the test results are shown in Table 1.
[0110] Embodiment 27
[0111] The process steps are the same as those in Example 1, except that: Step 4) the electrospinning parameters are as follows: voltage 30 KV, injection speed 0.12 ml / h, distance 5 cm; the test results are shown in Table 1.
[0112] Embodiment 28
[0113] The process steps are the same as those in Example 1, except that: Step 4) the electrospinning parameters are as follows: voltage 30 KV, injection speed 0.12 ml / h, distance 9 cm; the test results are shown in Table 1.
[0114] Table 1
[0115] <![CDATA[Density g / cm 3 > Fiber diameter nm Thermal conductivity W / (m·K) Example 1 0.020 100 0.040 Example 2 0.025 150 0.050 Example 3 0.015 70 0.020 Example 4 0.024 120 0.045 Example 5 0.018 90 0.025 Example 6 0.030 180 0.055 Example 7 0.023 110 0.043 Example 8 0.030 130 0.046 Example 9 0.018 80 0.022 Example 10 0.023 130 0.046 Embodiment 11 0.015 60 0.018 Example 12 0.022 100 0.048 Embodiment 13 0.020 120 0.050 Embodiment 14 0.030 220 0.055 Embodiment 15 0.018 90 0.035 Example 16 0.017 90 0.032 Embodiment 17 0.025 130 0.046 Embodiment 18 0.016 70 0.050 Embodiment 19 0.012 70 0.055 Embodiment 20 0.020 80 0.038 Embodiment 21 0.025 120 0.045 Embodiment 22 0.040 300 0.060 Embodiment 23 0.020 120 0.043 Embodiment 24 0.030 150 0.055 Embodiment 25 0.035 200 0.060 Embodiment 26 0.032 180 0.057 Embodiment 27 0.038 240 0.070 Embodiment 28 0.040 300 0.080
[0116] It can be seen from the test data shown in Table 1 above that in all embodiments of the present invention, zirconium carbide ceramic organic precursor is used as the raw material to prepare the spinning solution. The aerogel products obtained by electrospinning, pressing and pyrolysis have excellent performance and their density is ≤0.04g / cm 3, thermal conductivity is ≤0.08W / m·K, and fiber diameter is ≤300μm.
[0117] Furthermore, by optimizing the process, the distance parameter of the electrospinning is strictly controlled within 6.5 to 7.5 cm, and the process parameters of voltage and injection speed are coordinated to reduce the thermal conductivity of the aerogel to below 0.06 W / m·K, as shown in Examples 1 to 26.
[0118] Furthermore, the preparation process of zirconium carbide ceramic organic precursor is strictly controlled by optimizing the process, and the range of precursor process parameters is reasonably controlled to make its density ≤0.03g / cm 3 , thermal conductivity is ≤0.055 W / m·K, and fiber diameter is ≤150 μm, such as Examples 1 to 5, Examples 7 to 9, Examples 11 to 13, Examples 15 to 21, and Examples 23 and 24.
[0119] Furthermore, the preparation process of zirconium carbide ceramic organic precursor is strictly controlled by optimizing the process, and the range of precursor process parameters is reasonably controlled to make its density ≤0.022g / cm 3 , thermal conductivity is ≤0.055 W / m·K, and fiber diameter is ≤100 μm, such as in Example 1, Example 3, Example 5, Example 9, Examples 11 and 12, Examples 15 and 16, and Examples 18 to 20.
[0120] Furthermore, the preparation process of zirconium carbide ceramic organic precursor is strictly controlled by optimizing the process, and the density is ≤0.02g / cm by reasonably controlling the process parameter range of the precursor. 3 , thermal conductivity is ≤0.04 W / m·K, and fiber diameter is ≤100 μm, as in Example 1, Example 3, Example 5, Example 9, Example 11, Examples 15 and 16, and Example 20.
[0121] Furthermore, the preparation process of zirconium carbide ceramic organic precursor is strictly controlled by optimizing the process, and the range of precursor process parameters is reasonably controlled to make its density ≤0.015g / cm 3 , thermal conductivity is ≤0.02W / m·K, and fiber diameter is ≤70μm, as in Examples 3 and 11.
[0122] Furthermore, the preparation process of zirconium carbide ceramic organic precursor is strictly controlled by optimizing the process, and the range of precursor process parameters is reasonably controlled to make its density ≤0.015g / cm 3 , thermal conductivity is ≤0.018 W / m·K, and fiber diameter is ≤60 μm, as shown in Example 11.
[0123] The numerical range described in the present invention includes all the numerical values within the range, and includes the range value formed by any two numerical values within the range. Different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0124] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0125] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing zirconium carbide nanofiber aerogel, characterized in that: It includes the following steps: S11 adding zirconium carbide ceramic organic precursor into a binder and stirring evenly to obtain a spinning solution; S12 electrospinning the spinning solution, drying, and pressing to obtain a zirconium carbide nanofiber aerogel blank; S13 heat treatment to obtain zirconium carbide nanofiber aerogel.
2. The preparation method according to claim 1, characterized in that: The steps for preparing the zirconium carbide ceramic organic precursor are as follows: S21: adding zirconium oxychloride into a mixed solvent of water and ethanol to cause a hydrolysis reaction; S22 adds acetylacetone to the hydrolysis reaction solution to react and obtain enol acetylacetone; S23 adding butanediol to the reaction solution containing the enol acetylacetone to perform alcohol exchange; S24 is evaporated to obtain an organic precursor of zirconium carbide ceramic.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the zirconium oxychloride, the mixed solvent, acetylacetone and butanediol is 1:2-4:3-5:1-3.
4. The preparation method according to claim 1, characterized in that: The binder comprises anhydrous ethanol and polyvinyl pyrrolidone; based on the mass of the anhydrous ethanol being 100%, the mass percentage of the polyvinyl pyrrolidone is 5-20%.
5. The preparation method according to claim 4, characterized in that: In the spinning solution, the mass ratio of the zirconium carbide ceramic organic precursor to the anhydrous ethanol is 1:0.4-0.
6.
6. The preparation method according to claim 1, characterized in that: The process parameters of the electrospinning are as follows: voltage is 25-30 Kv, injection speed is 0.10-0.15 ml / h, and distance is 6-8 cm.
7. The preparation method according to claim 1, characterized in that: The steps of the heat treatment are as follows: S71 is kept at 500-700℃ under vacuum for 1-2h; S72, under vacuum conditions, heat to 1000-1500°C at a rate of ≥1°C / min and keep warm for 1-2h; S73 Cool down to room temperature.
8. A zirconium carbide nanofiber aerogel, characterized in that: Its diameter is ≤100nm and its density is ≤0.02g / cm 3 , thermal conductivity ≤0.04W / m·K.
9. The zirconium carbide nanofiber aerogel according to claim 8, characterized in that: The aerogel is prepared by the method for preparing the zirconium carbide nanofiber aerogel according to any one of claims 1 to 7.
10. Use of the zirconium carbide nanofiber aerogel according to claim 8 or 9 in the fields of aerospace, high temperature resistant materials or thermal insulation materials.
Citation Information
Patent Citations
Nano zirconium carbide ceramic powder and preparation method thereof
CN103121844A
Ceramic carbide fiber, method for making the ceramic carbide fiber and application of the ceramic carbide fiber
WO2010130272A1